Proteomic Analysis of Protein Ubiquitination Events in Human Primary and Metastatic Colon Adenocarcinoma Tissues - Zhang, Yi; Chen, Cong; Yu, Tingting; Chen, Tao (Frontiers in Oncology, 2020)
Protein ubiquitination is essential for multiple physiological processes through regulating the stability or function of target proteins and has been found to play critical roles in human cancers. However, the protein ubiquitination profile of human metastatic colon adenocarcinoma tissue has not been elucidated yet. In this study, a proprietary ubiquitin branch (K-ε-GG) antibody-based label-free quantitative proteomics and bioinformatics were performed to identify the global protein ubiquitination profile between human primary (Colon) and metastatic colon adenocarcinoma (Meta) tissues. A total of 375 ubiquitination sites from 341 proteins were identified as differentially modificated (|Fold change|>1.5, p<0.05) in Meta group compared with the Colon group. Among them, 132 ubiquitination sites from 127 proteins were upregulated and 243 ubiquitination sites from 214 proteins were downregulated in Meta group. Fifteen ubiquitination motifs were found. Furthermore, GO and KEGG pathway analysis indicated that proteins with altered ubiquitination in Meta group were enriched in pathways highly related to cancer metastasis, such as RNA transport and cell cycle. We speculate that the altered ubiquitination of CDK1 may be a pro-metastatic factor in colon adenocarcinoma. This study provides novel scientific evidences to elucidate the biological functions of protein ubiquitination in human colon adenocarcinoma and insights into its potential mechanisms of colon cancer metastasis, which would be helpful to discover novel biomarkers and therapeutic targets for effective treatment of colon cancer.